Towards Eurasia: remapping Europe as 'upstart peripheral to an ongoing operation'. Issue 2 (3rd April 2019) - Gasser, Lucy
ABSTRACT: In order to heed the call in world literature studies to work against disciplinary Eurocentrism by refiguring both what constitutes world literature and how this is read, in this article I propose world literature as an archive of world-making practices and as an impulse for the articulation of alternative methodological approaches. This takes world literature from the postcolonial South as, following Pheng Cheah, instantiating a modality of world literature in which the need for imagining worlds with alternative centres to those determined by coloniality is particularly acute. A response to this is facilitated and illustrated by a reading of Bengali poet Rabindranath Tagore's Letters from Russia (1930), and South African writer/activist Alex La Guma's A Soviet Journey (1978). By drawing forward connections between the postcolonial South and the former Soviet Union, this complicates traditional colonial arrangements of the colonial 'centre' as cradle of civilisation and culture, as well as postcolonial scholarship's cumulative fetishisation of 'Europe', by allowing a reshuffling of the co-ordinates determining 'centres' and 'peripheries' and a more nuanced grasp of 'Europe' simultaneously. These imaginative journeys destabilise 'Europe' as closed category and call forth Eurasia as a more appropriate categorical–cartographical framework for thinking this space and the connections and (hi)story-telling it stages and fosters.